Nilai-Nilai Pendidikan Akhlak pada Film Sang Kiai terhadap Penanaman Akhlak dalam Dunia Pendidikan Islam Kontemporer - Rana Farras Irmi; Salminawati Salminawati; Zaini Dahlan (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to describe the positive impact of the development of television through film, especially in presenting deep moral values. The research method used is Library Research with a qualitative approach. Data was collected through written sources, especially book texts in libraries and information from the internet, which relate to educational values ​​and morals. The focus of this research is on the values ​​of Moral Education contained in the film "Sang Kiai" by Rako Prijanto. Analysis of this film reveals the depth of the moral message connected to Islamic values ​​from the books of classical scholars. The research results show that "Sang Kiai" is not only entertainment, but also conveys a deep moral message, in accordance with the teachings of classical Islamic literature. The significant contribution of this film in the context of contemporary Islamic education lies in its role as a tool for teaching moral values. This research provides in-depth insight into how films such as "Sang Kiai" substantially convey the values ​​of moral education, relate them to classical Islamic literature, and contribute to modern Islamic education. The conclusion of this research is that works of art such as films have an important role in spreading and strengthening moral values ​​in society. Films, such as "Sang Kiai", have the potential to become vital instruments in moral education in the future. The prospects of this research indicate that film can be an effective means of conveying moral values ​​in modern Islamic education, with the potential to provide a significant positive impact.